1991
DOI: 10.1107/s0108767391002441
|View full text |Cite
|
Sign up to set email alerts
|

The joint probability distribution of structure factors incorporating anomalous-scattering and isomorphous-replacement data

Abstract: A method to derive joint probability distributions of structure factors is presented which incorporates anomalous-scattering and isomorphous-replacement data in a unified procedure. The structure factors F, and F_n, whose magnitudes are different due to anomalous scattering, are shown to be isomorphously related. This leads to a definition of isomorphism by means of which isomorphous-replacement and anomalous-scattering data can be handled simultaneously. The definition and calculation of the general term of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The evaluations of (13) and (14) can be performed in a standard way (see, for example, Peschar, 1991) and result in…”
Section: =Rir2r3(etr)-65 ~ ~ ~ ~ I Rjp2r3mentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluations of (13) and (14) can be performed in a standard way (see, for example, Peschar, 1991) and result in…”
Section: =Rir2r3(etr)-65 ~ ~ ~ ~ I Rjp2r3mentioning
confidence: 99%
“…An important goal of the paper is the derivation of a new expression to estimate the triplet phase sums present among isomorphous data. It will be shown that the new procedure, supplemented by optimal doublet phase-sum estimates that use difference Patterson information [Kyriakidis, Peschar & Schenk (1993b), from now on referred to as KPS2], leads to far better results than obtainable by other j.p.d.-based expressions (Hauptman, 1982a, b;Giacovazzo, 1983;Giacovazzo, Cascarano & Zheng, 1988;Fortier & Nigam, 1989;Peschar & Schenk, 1991;hereafter P&S), in particular if the DR is small (Kyriakidis, Peschar & Schenk, 1993a; from now on KPS 1). In contrast with other DM techniques, the final triplet distributions in the SAS and 2DW cases seem to be of sufficient quality to be used in a normal DM procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Let us define a set of p isomorphous structure factors, (2) in accordance with Peschar & Schenk (1991) …”
Section: The Algebraic Estimation Of the Doublet Phase Sumsmentioning
confidence: 99%
“…Fortier & Nigam (1989) rationalized the similar expressions for the joint probability distributions (j.p.d.s) to be a result of isomorphous data sets. Recently, the full probabilistic integration of DM with any number and type of isomorphous data sets has been accomplished (Peschar & Schenk, 1991). Although test results (Furey, Chandrasekhar, Dyda & Sax 1990) exist which suggest that DM may be applicable in solving protein structures ab initio, the full potential of DM in this respect seems not to have been realized as yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation